First experience of laparoscopic colon resection with primary anastomosis for combat-related thoracoabdominal trauma with through-and-through colon injury - Mikheiev, Iu. O.; Gumeniuk, K. V.; Tielushko, Ya. V.; Mialkovskyi, D. S.; Savchenko, S. I.; Міхеєв, Юрій Олександрович; Гуменюк, К. В.; Тєлушко, Ярослав Володимирович; Мялковський, Д. С.; Савченко, Сергій Ігорович (Запорізький державний медико-фармацевтичний університет, 2025)
Aim: to demonstrate the possibilities and advantages of laparoscopic surgery in combat-related abdominal penetrating trauma with colon injury. Materials and methods. This case report presents the first experience of laparoscopic colon resection with primary anastomosis for combat-related thoracoabdominal trauma with through-and-through colon injury. A 47-year-old serviceman sustained an explosive penetrating thoracoabdominal injury (dropping explosives from a drone) operated 10 hours after. Initial management at Role 2 included chest tube drainage, surgical debridement, and wound sealing of the chest. CT: penetrating gunshot wound with internal and external damage to the lower lobe of the left lung, perforation of the diaphragm on the left, and transverse colon perforation with a retained metal fragment, pneumoperitoneum, drained hemopneumothorax, and a gunshot fracture of the posterior third of the 5th left rib. Exploratory laparoscopy revealed no free fluid in the abdominal cavity. Surgery: the diaphragmatic perforation was sutured with a 3-0 V-loc barbed suture, the segment of the transverse colon was resected using two Endo-GIA 60 linear staplers according to the severity of injury (AAST Grade 3) and non-viable edges of colon wound. To ensure mobility, a side-to-side antiperistaltic anastomosis was performed using an Endo-GIA 60 stapler (blue cartridge). The anastomosis site was reinforced with a single-layer 3-0 V-loc suture. The procedure was completed with abdominal drainage and port site closure. Мета роботи – продемонструвати можливості та переваги лапароскопічної хірургії при бойовій проникній травмі живота з пошкодженням товстої кишки. Матеріали і методи. Цей клінічний випадок є першим досвідом лапароскопічної резекції товстої кишки з первинним анастомозом при бойовій торакоабдомінальній травмі з наскрізним ушкодженням товстої кишки. Військовослужбовець віком 47 років отримав вибухове проникне торакоабдомінальне поранення (скид з дрону) та прооперований через 10 годин. Первинна допомога на другому рівні включала дренування плевральної порожнини, хірургічну обробку та герметизацію рани грудної клітки. Результати КТ: наскрізне вогнепальне поранення з наскрізним пошкодженням нижньої частки лівої легені, пошкодженням лівого куполу діафрагми, наскрізним пораненням поперечної ободової кишки з наявністю металевого осколка, пневмоперитонеум, дренований гемопневмоторакс, вогнепальний перелом задньої третини V ребра зліва. Під час оглядової лапароскопії вільної рідини в черевній порожнині не виявлено. Операція: поранення діафрагми зашите шовним матеріалом 3-0 V-loc; враховуючи тяжкість травми (3 ступінь за AAST) і нежиттєздатність країв, здійснили резекцію сегмента поперечно-ободової кишки за допомогою двох лінійних ендоскопічних степлерів Endo-GIA 60; беручи до уваги достатню мобільність, виконано антиперистальтичний анастомоз бік-у-бік за допомогою лінійного степлера Endo-GIA 60 (блакитний картридж). Технічний отвір зашито одношаровим швом 3-0 V-loc. Надалі здійснили дренування черевної порожнини та ушивання портів.
Перший досвід лапароскопічної резекції ободової кишки з первинним анастомозом при бойовій торакоабдомінальній травмі з наскрізним пошкодженням ободової кишки
Keywords: war-related trauma; thoracoabdominal trauma; laparoscopic anastomosis; linear endoscopic stapler; бойова травма; торакоабдомінальна травма; лапароскопічний анастомоз; лінійний ендоскопічний степлер